Gender gaps in Spain: Family issues and the career development of college educated men and women - Ainara González de San Román; Sara de la Rica (Institute for the Study of Labor (IZA), 2012)
Our goal in this paper is to focus on highly educated men and women and try to explore the trade-offs between family and working career in Spain, where changes in female behavior with respect to the labor market have been relatively recent but rather important. We compare male and female behavior with respect to labor supply and labor performance along their life cycle for different birth cohorts to explore the connection between family and work over time. Our results indicate that family plays a crucial role as a source of gender differences in the labor market in Spain. By 2008, children are the main determinant of the observed gap in labor supply between college men and women. Furthermore, with respect to hours worked, children are also an important determinant for the decision of college - educated mothers to choose to work part - time. However, children do not seem to contribute to explain the observed gender wage gap (5%) between college men and women.
Keywords: J12; J2; J3; 330; gender gaps; career development; family and work; Spain; Geschlechterdiskriminierung; Akademiker; Erwerbsverlauf; Familie-Beruf; Weibliche Arbeitskräfte; Spanien